New possibilities in Pectus Excavatum - Chudzik, Robert; Jarosz-Chudzik, Katarzyna; Gołębiowska, Maria; Gołębiowska, Beata; Kulczyński, Marcin (Journal of Education, Health and Sport, 2018)
Pectus Excavatum is one of the most frequent deformations of the chest wall, diagnose and surgical treatment mainly in pediatric patients (1:300 - 1:1000 live births). More often in men than in women, the etiology of this disease is not entirely clear, probably multifactorial.The aim of the study was to analyze the current literature regarding the surgical treatment of pectus excavatum and to indicate new treatment options.For the purpose of this study, we analyzed the current papers on pectus excavatum found in the PubMed database. The Ravich and Nuss procedure remains the basic way to treat pectus excavatum, and over the years both methods have found their supporters. The work focused on the improvement of both of these methods, however, mainly the Nuss Procedure was considered, becasue of be minimally invasive. Attention was also paid to the possibility of simultaneous implementation of both methods and advantages of this way for the patients. The new possibilities concern not only the surgical techniques itself, but also the new technical possibilities used in surgery.Nowadays, the scientific focuses on improving currently used methods by reducing operational risk, shortening the time of surgery, and thus improving patient safety and, of course, improving its quality of living. Most likely, with the development of technology, further options will be adapted to the treatment of Pectus Excavatum.